Saberes de diretores sobre as dimensões da administração escolar - Silva, Caroline Miranda Palmieri da (2022)
This study aimed to analyze the relationship with Knowledge, according to Bernard Charlot, of school directors according to the school administration model of Benno Sander (2007), with the economic, pedagogical, political and cultural dimensions. Data were collected in 2021, through two instruments: a closed questionnaire, in a stratified sample, composed of 2882 Brazilian directors and a focus group with five mentor directors (representing the five regions of Brazil) who participated in the Mentoring Improvement Course of School Directors offered by the Federal University of São Carlos (UFSCar). There was an intertwining between the relationship with the Knowledge of the five directors and the dimensions of Sander (2007), especially, the Knowing how to do and the relational Knowledge. The directors respond to the extent of what they experience and to analyze the relationship of a subject with Knowledge is to understand the epistemic, social and identity relationships of this being immersed in the learning process, and these dimensions are not fragmented in this process. Future studies are indicated in order to closely monitor the management of these directors in different regions of Brazil, mainly due to the diversity of Brazilian schools. It is concluded that, in Brazil, public policies need to promote democratic management, instituting forms of entry into management positions through democratic means, both in secretariats and in institutions, since it is essential that these directors can be legitimate representatives in the fight for a quality education, in addition to having more spaces in which debates take place in municipal, state and federal instances, in which more democratic and legitimate discussions are held, with the intention of thinking about a different school from the one we have today.